Importance of meniscal injury diagnosis and surgical management in dogs during reconstruction of cranial cruciate ligament rupture: A retrospective study - Seo, Seok-Beom; Rahman, Md. Mahbubur; Jeong, In Seong (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The objective of this study was to evaluate the benefits of the clinical outcome of meniscal injury diagnosis and surgical management during the reconstruction of cranial cruciate ligament rupture (RCCL) in dogs. Materials and methods: For these purpose two groups with 2 different surgery regimens; group 1 (G1), RCCL was corrected with partial meniscectomy and tibial tuberosity advancement (TTA), and another one (group-2, G2) only with TTA. Long-term follow-up about postoperative complications and any recurrence of signs were recorded by referring veterinarians by medical questionnaire over telephone contact and radiographic postoperative follow-up of bone healing was evaluated. Results: Meniscal injuries were diagnosed arthroscopically in five dogs out of six dogs, and corrected by partial meniscectomy arthroscopically. The percentage of presence of meniscal injury was 83%. It was found that clinical outcomes were superior in G1 than G2 group both walking starting time (4.6±2.5 and 6.4±2.9 days, respectively) or full recovery time (39.2±26.9 and 58.1±24.5 days, respectively) was significantly shortage (P<0.05) along with less postoperative complication at two years postoperative observation. Out of the five dogs, lameness, arthritis was developed in four dogs in G2 group while the number of dogs was two in G1 group within two years. Conclusion: Finally based on the clinical superiority, it is recommended that meniscal injury should be checked and corrected during RCCL reconstruction for getting better clinical outcomes. http://doi.org/10.5455/javar.2017.d223